Strawberry plant feeding: tips on fertilizing strawberry plants - Pryimak, D. I. (ТДАТУ, 2019)
Strawberries are resilient and can grow in many different settings. Knowing when and how to fertilize strawberry plants will ensure a bountiful harvest and provide the biggest yields.
Keywords: strawberries; nitrogen; the soil is wet; water treatment